(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The present study aims to fill a significant need in the existing research literature byconducting a thorough analysis of the economic consequences of immigration on host nations. Whilethe current body of literature extensively examines the economic impacts of immigration, this studyprovides a comprehensive framework that incorporates several aspects such as labor market patterns,wage fluctuations, fiscal measures and provision of social services. The technique used in this study isbased on utilization of secondary sources, which allows for a comprehensive comprehension of thecomplex interplay between the immigration and its economic impacts. The results of the study indicatesthat the effect of immigration on the salaries of the native workers is contingent upon may variables,including the skill mix of the workforce, the level of labor market rigidity and the degree ofsubstitutability between immigrant and native workers.This research further examines the impact offiscal policy and social services, especially evaluating the extent to which immigration may exertpressure on welfare systems relative to tax payments. The study emphasizes the need of adoptingcomplex policy considerations that take into account many elements such as educational background ofthe immigrants. Through the identification and resolution of information gaps, the present researchcontributes to a more comprehensive approach to policy-making and enhances our comprehension ofeconomic impact of immigration on host country in various aspects.